Psychosocial research in the diabetic foot: Are we making progress?. (18th December 2019) - Vileikyte, Loretta; Pouwer, Frans; Gonzalez, Jeffrey S
Abstract: Background/Methods: This review summarizes recent advances regarding the role of psychological factors in people with a diabetic foot ulcer (DFU). It describes the detrimental effects of diabeticfoot complications and in particular, Charcot Neuroarthropathy (CN), on health status and quality of life (QoL) and emphasizes the importance of utilizing DFU‐specific assessment tools. Results: Diabetic neuropathy (DN)‐related postural instability is key in generating depression in high DFU risk patients and in predicting offloading non‐adherence those with active DFUs. Patients' views of their own DFU risk are largely inconsistent with biomedical models, resulting in a lack of preventive foot self‐care. Furthermore, DFUs are a source of specific emotional responses, with fear of amputation predominant. While fear of amputation is associated with better preventive foot self‐care, it appears to be linked to DFU non‐healing, though mechanisms are yet to be elucidated. Until now, systemically released stress hormones were recognized as the only biological mechanism through which psychological stress influences healing. Recently, the skin has been found to be an extra‐adrenal site for glucocorticoid synthesis with local, tissue‐specific cortisol implicated in DFU non‐healing. Conclusions: These observations could potentially lead to future targets for therapeutic and psychological interventions.